Deep venous thrombosis due to massive compression by uterine myoma - Brucka, Aleksandra; Szyłło, Krzysztof; Stefańczyk, Ludomir; Dobrowolski, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2010)
A 42-year-old woman, gravida 3, para 3 was admitted to hospital because of painful oedema of her right lower extremity. Initial physical examination revealed a gross, firm tumour filling the entire peritoneal cavity. Doppler ultrasound scan revealed a thrombus in the right common iliac vein, extending to the right femur and popliteal veins, and partially into the calf deep vein. Computed tomography confirmed the existence of an abdominal tumour probably deriving from the genital organs and the presence of a thrombus in the said veins. The patient underwent hysterectomy where a myomatous uterine was removed. She was put on subcutaneous enoxaparine and compressive therapy of the lower extremities. Such symptoms as pain and oedema receded. Control Doppler scan showed fibrinolysis, partial organization of the thrombus and final vein recanalisation. After exclusion of other risk factors of deep vein thrombosis apart from stasis, we conclude that the described pathology was the effect of compression of regional pelvic structures by a uterine myoma. Key words: uterine myoma, deep venous thrombosis.